2012
DOI: 10.4103/2141-9248.96930
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of orthodontics as a dental specialty: A preliminary survey among LASUCOM students

Abstract: Background:Awareness of malocclusion and the need to make corrections has increasingly becomes prevalent among our population. However, very few patients have presented in the orthodontic clinics with referrals from medical practitioners, an indication that the primary caregivers may be deficient in the knowledge of orthodontic practice.Objective:To assess the knowledge of orthodontics and the awareness of the effects of malocclusion on the general well-being, among medical students at the Lagos State Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
11
1
1
Order By: Relevance
“…(AlShahrani, 2014) In Africa a study suggested basic orthodontic knowledge to undergraduate students to stimulate their interest in the field as well as to be aware of the correct timings for referral patients. (Adegbite, Ogunbanjo, Ajisafe, & Adeniyi, 2012) Interesting studies concerning the orthodontic treatment of pediatric patients have been carried out in Iran and Saudia Arabia which again had similar outcomes as previous studies. (Aldrees et al, 2015;Sajadi, Torabi, Poreslami, & Babei, 2016) One study performed in the UK however, had different results showing that undergraduates in the UK were well prepared in the field of orthodontics and felt confident enough to deal orthodontic emergencies.…”
Section: Figure 2 Responses To Questions In the Skills Sectionmentioning
confidence: 58%
“…(AlShahrani, 2014) In Africa a study suggested basic orthodontic knowledge to undergraduate students to stimulate their interest in the field as well as to be aware of the correct timings for referral patients. (Adegbite, Ogunbanjo, Ajisafe, & Adeniyi, 2012) Interesting studies concerning the orthodontic treatment of pediatric patients have been carried out in Iran and Saudia Arabia which again had similar outcomes as previous studies. (Aldrees et al, 2015;Sajadi, Torabi, Poreslami, & Babei, 2016) One study performed in the UK however, had different results showing that undergraduates in the UK were well prepared in the field of orthodontics and felt confident enough to deal orthodontic emergencies.…”
Section: Figure 2 Responses To Questions In the Skills Sectionmentioning
confidence: 58%
“…The purpose of the present study was to assess the level of orthodontic knowledge and awareness among the undergraduate medical students in Bharath Institute of higher Education & Research, Sree Balaji medical college & hospital. Although dental malocclusion in itself is neither a disease nor a life-threatening condition, but it has some significant impact on the physical, emotional and psychosocial health of the person [12] . People with severe malocclusions have more severe periodontal diseases, temporomandibular joint (TMJ) disorders and decreased masticatory load efficiency [13] .…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Adegbite et al [14] involving medical trainees of the year second to sixth, only 45.9% of the trainees had heard about orthodontics. When they were asked to identify the appliances used in orthodontic treatment only 57.7% selected the braces.…”
Section: Discussionmentioning
confidence: 99%